Տեքստը որպես շարահյուսական միավոր - Տաթևիկ Սաֆարյան (ՀՀ ԳԱԱ հրատ.)
Текст – это завершенный письменный документ, который имеет заголовок, особые структуральные единицы, связанные лексическими, грамматическими, стилистическими признаками, имеющими прагматическую целенаправленность. A text is a completed written document having a title and special structural items interconnected with lexical, grammatical and stylistic characteristics with functional objectives.
Keywords: Philology; Linguistics; Language and Literature